Strategi Pemasaran Digital Terintegrasi untuk Membangun Digital Trust pada UMKM Jasa Konstruksi - Lady; Ardianata, Kristi; Ariyanto, Hepy Hefri (Jurnal PubBis, 2026)
The evolution of digital media requires MSMEs, particularly in the custom construction service sector, to adopt digital marketing strategies to build visual credibility and expand market reach. This study aims to analyze the implementation of an integrated digital marketing strategy through Instagram, Facebook, WhatsApp Business, a website, and Google Maps at Nicko Kaca & Aluminium. A descriptive qualitative case study method was employed, where data were collected through observation, digital insight documentation, and interviews with six informants consisting of one business owner and five customers. Data analysis was conducted through four interactive stages including data collection, data condensation, data display, and conclusion drawing and verification. The results show that the implementation of this digital ecosystem significantly increased business visibility, which the Instagram Ads platform contributed an 85% reach rate out of a total of 3,230 new audience members. Meanwhile, other platforms such as Google Maps, the website, and Facebook provided value in the credibility dimension through physical location verification and visual portfolios, which served as determining factors for consumer trust. This research produces the Digital Trust Funnel model, which synergizes the visibility, credibility, and conversion stages. The implications of this study emphasize that building an interconnected digital ecosystem can mitigate information asymmetry and establish consumer trust in service industries with high levels of uncertainty